Survey of Cybersecurity in Smart Grids Protocols and Datasets - Muhammad, Mamdouh; Alshraa, Abdullah; German, Reinhard (Procedia Computer Science, 2024)
Smart grids are two-way communications grids that converge Information Technology (IT) and Operational Technology (OT) to transfer energy-related information between different industry components within the grid. Smart grids have changed the energy sector by increasing sustainability, efficiency and integrating renewable energy sources. However, smart grids are vulnerable to IT-related attacks because they rely on Information and Communication Technology (ICT). By surveying relevant papers and evaluating accessible statistics, this study explores cybersecurity in smart grids by examining current communication protocols and standards. We carefully compile various datasets with general information about four of the most smart grid-related datasets. Our study and conclusions address the key components of a smart grid and offer information that can help create cybersecurity plans specifically for smart grids. This research contributes to the discourse on smart grid security, which is important for preserving the stability of contemporary energy systems.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Cyber-Physical Systems; cybersecurity; Information Technology; IT/OT convergence; smart grids